(untitled) (Clinics, 2021)
OBJECTIVES: Antineutrophil cyto plasmic antibody-associated vasculitis (AAV) is a fatal disease. Currently, predictors of mortality due to AAV are based on the distribution of organ involvement. The novel fibrosis index (NFI) is an index composed of laboratory results that reflect the degree of liver fibrosis. This study aimed to evaluate whether NFI can predict poor outcomes in patients with AAV without substantial liver disease. METHODS: A total of 210 patients with immunosuppressive drug-naı¨ve AAV were retrospectively reviewed. NFI was calculated as follows: NFI=(serum bilirubin (alkaline phosphatase)2 )/(platelet count (serum albumin)2 ). NFI cut-off was set at 1.24 (the highest quartile). Poor outcomes were defined as all-cause mortality, relapse, and end-stage renal disease (ESRD). RESULTS: During the median 34.5 months of follow-up, 21 patients (10%) died, 72 patients (34.3%) relapsed, and 38 patients (18.1%) had ESRD due to AAV progression. The median calculated NFI was 0.61, and it was higher in AAV patients with all-cause mortality than in those without mortality, but the difference was not statistically significant (1.26 vs. 0.59). AAV patients with NFI at diagnosis X1.24 exhibited a significantly lower cumulative patient survival rate than those with NFI at diagnosis o1.24 (p=0.002). Multivariate Cox hazard model analysis showed that NFI at diagnosis X1.24 was an independent predictor of all-cause mortality in AAV (hazard ratios [HR] 2.850, 95% confidence interval [CI] 1.026, 7.910). CONCLUSIONS: NFI X1.24, which may be an independent predictive marker for all-cause mortality in AAV patients without substantial liver disease.